Analisis Pengendalian Persediaan Bahan Baku dengan Metode Material Requirement Planning pada Pabrik Roti Arum di Kecamatan Kota Waingapu Sumba Timurnusa Tenggara Timur - Trisno, Ahmad; Sunarso (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Every business, particularly those in the food sector, is inherently involved in production activities and is required to produce high-quality products to satisfy consumer expectations. This production process depends heavily on the control of raw materials. Effective raw material control is crucial for a company to develop its operations and also impacts cost efficiency, profitability, and production smoothness. This study aims to analyze the application of the Material Requirements Planning (MRP) method in optimizing raw material inventory costs at the Arum Bakery in Waingapu. The research employs a case study design to conduct an in-depth analysis of production practices at the Arum Bakery in Waingapu. The data utilized include primary data obtained through observations, interviews, and documentation, as well as secondary data from various sources. Data analysis is performed using the MRP method to identify and evaluate raw material needs and production processes. The results indicate that the inventory costs calculated using the Lot-for-Lot method amount to IDR 600,000.00, the Economic Order Quantity (EOQ) method amounts to IDR 1,111,600.00, the Period Order Quantity (POQ) method amounts to IDR 2,008,800.00, and the Company Policy method amounts to IDR 2,710,000.00. Based on these results, the inventory costs under the company's policy are higher compared to those using the MRP methods. The most efficient MRP method is the Lot-for-Lot method, as it results in the lowest costs, thereby confirming the hypothesis